The Summer Undergraduate Research Experience as a Work-Integrated Learning Opportunity and Potential Pathway to Publication in Psychology - Golding, Raelee M.; Breen, Lauren J.; Krause, Amanda E.; Allen, Peter J. (Frontiers in Psychology, 2019)
Unlike disciplines which focus on skills development from year one of a bachelor’s degree, training in psychology in Australia follows the scientist-practitioner model. According to this model, an undergraduate psychology degree should focus on the scientific principles underpinning the discipline and provide a foundation for the development of professional skills in graduate school. However, most Australian psychology undergraduates do not continue into graduate school, and concerns have been raised about their lack of applied skills and work-readiness. Work integrated learning (WIL) refers to strategies aimed at providing students with practical experiences (e.g., fieldwork, placements, internships) directly related to their course of study. The objective of WIL is to increase work-readiness. Accreditation standards coupled with the norms of the discipline have historically prevented the inclusion of typical WIL experiences in Australian undergraduate psychology degrees. However, one particular type of WIL activity – the undergraduate research experience (URE) – is particularly suited to psychology. In a typical URE, students collaborate with faculty to conduct research designed to make an original contribution to their field. The current study is a qualitative investigation of stakeholder perceptions of a competitive summer URE program ran from 2012 to 2016. Six faculty members and seven undergraduate students were engaged in semi-structured interviews about their URE experiences. Constructed themes broadly reflected the benefits and challenges of the program, and included work-readiness and additional research experience, networking and teamwork, publication, quality of experience and equity of opportunities. Faculty members and students spoke favourably of their UREs in most cases, although issues of administration and financial concerns were mentioned consistently, as were concerns about the length, timing and nature of projects. Students reported skills development and networking as two of the key benefits of their participation in the program, and article publication was seen as particularly beneficial to career prospects. Our findings suggest that student co-authored publications resulting from UREs are possible, but careful thought is required to optimise their likelihood. Overall, this research adds to a growing literature suggesting that UREs can confer a range of benefits to Australian psychology schools related to increased research capacity and student satisfaction.